Der Wasserhaushalt eines Kiefernwaldes und Wechselwirkungen mit dem Energiehaushalt.: Eine klimaökologische Studie aus dem Trockengebiet der südlichen Oberrheinebene - Kessler, Albrecht; Müller, Roland; Jaeger, Lutz (ERDKUNDE, 1988)
The investigations here are considered as a contribution to the climatic ecology in the dry region of the southern Rhine valley plain. This is done by means of long-standing observations. The ecosystem there is a rapidly growing pine forest in the former, now dry alluvial valley of the river Rhine. Besides the conventional elements of the climate special regard is paid to the components of the water balance, namely to the water content of the soil, to interception, transpiration, precipitation within the stand, and also to the components of the heat balance equation. The stem flow amounts to 3.1% of the precipitation above canopy. The long-standing mean falls to 64% to the precipitation within the stand and to 36% to the interception. The interception is a nearly invariant term regarding half-yearly values. The soil-water content shows a simple yearly pattern with a minimum in the main vegetation period. It is governed by the precipitation within the stand and the evapotranspiration . The infiltration rate can be ignored. The evapotranspiration or the latent heat is linked to the heat balance equation with the other components which are net radiation, sensible heat flux and heat flux into the ground. The mean annual pattern of these terms and their interannual variability are presented here. We can express the big influence of the water regime to the energy balance. We can show further that the high evapotranspiration rates in winter cannot be explained by the net radiation, but primarily by the sensible heat flux, which is directed to the canopy. The yearly means amount to the following values J/cm² d): net radiation: 680, latent heat flux: -391,sensible heat flux: -291, heat flux to the ground: 2.